RHETORICAL STRUCTURE ANALYSIS OF DISCUSSION SECTIONS IN UNDERGRADUATE JOURNAL ARTICLES - Putri, Eno; Surlitasari, Desi; Adam (Universitas Islam Ogan Komering Ilir Kayuagung, 2025)
The rhetorical structure describes the interconnectedness between parts of a text to provide a coherent and logical presentation of arguments. In writing journal articles, students need to understand this concept, as it is important for clarifying the delivery of clear, logical, and convincing arguments, especially in the discussion section, where interpretation and articulation of scientific contributions are essential. However, previous studies have rarely focused on the rhetorical structure of undergraduate journal articles, especially in the academic field. This study aims to analyze the rhetorical structure of the discussion sections in journal articles written by undergraduate students, particularly those published in SINTA 3-accredited journals. The research was conducted at the University of the Riau Islands using a qualitative content analysis and thematic interpretation analysis. It breaks down the discussion section into six main moves and their accompanying sub-moves. The researcher analyzed ten undergraduate journal articles using documentation techniques and analytical coding sheets. The results of this study show that Move 2 (Reporting Results) and Move 4 (Commenting on Results) are the most used, whereas Move 5 (Drawing Conclusions) and Move 6 (Suggesting Future Research) appear infrequently. These findings suggest that students tend to focus more on presenting results but lack deeper interpretation and explicit articulation of their scientific contributions. Therefore, the author recommends that students use the rhetorical structure model as a reference to develop a more systematic, critical, and scholarly discussion section in their articles.